2013
DOI: 10.4103/2229-5178.115538
|View full text |Cite
|
Sign up to set email alerts
|

Ingenol mebutate: A novel topical drug for actinic keratosis

Abstract: The global incidence of non-melanoma skin cancer is rising. Significant morbidity leading to unacceptable cosmetic outcomes and/or functional impairment is a major concern. Search for non-surgical, non-invasive and tissue-sparing treatment modalities has led to development of new therapeutic agents. Actinic keratoses (AK) are one part of a continuous spectrum of benign sun damage to squamous cell carcinoma (SCC). Although it is not possible to predict which AK might progress to SCC, the presence of AK is a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Ingenol-3-angelate also inhibits HIV infection by downmodulating CD4 and CXCR4 receptors and enhances HIV-1 replication in chronically infected cells, reiterating the clinical application of ingenol compounds to HIV cure (Ersvaer et al, 2010; Hong et al, 2011; Olsnes et al, 2009). Other important medical effects obtained using ingenol derivates such as ingenol mebuate and ingenol 3,20-dibenzoate have been published (Aditya and Gupta, 2013; Racke et al, 2012). Our comparison of ING B with the latter compound showed that ING B was more efficient in activating HIV from latency than ingenol 3,20-dibenzoate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingenol-3-angelate also inhibits HIV infection by downmodulating CD4 and CXCR4 receptors and enhances HIV-1 replication in chronically infected cells, reiterating the clinical application of ingenol compounds to HIV cure (Ersvaer et al, 2010; Hong et al, 2011; Olsnes et al, 2009). Other important medical effects obtained using ingenol derivates such as ingenol mebuate and ingenol 3,20-dibenzoate have been published (Aditya and Gupta, 2013; Racke et al, 2012). Our comparison of ING B with the latter compound showed that ING B was more efficient in activating HIV from latency than ingenol 3,20-dibenzoate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results presented here, it would be expected that several rounds of treatments with ING B would result either in complete elimination of HIV or decrease in viral load to the point at which the immune system could complete the elimination of this pathogen. Several aspects favor ING B use as follows: (a) there would be abundant source of ingenol since the Brazilian Euphorbia tirucalli is easily grown in plantations; (b) ingenol derivatives have already been used therapeutically in humans to tackle diseases (Aditya and Gupta, 2013; Ersvaer et al, 2010) and their potential in HIV activation has been largely described (Fujiwara et al, 1998; Hong et al, 2011; Spitaler and Cantrell, 2004; Steinberg, 2008; Van Lint et al, 2013); (c) we obtained a proof of principle that ING B does reactivate latent HIV ex vivo . Additionally, this has also been proven in a study with Rhesus macaque model where it was shown that treatment with ING B could activate SIV mac 251 latency in Rhesus monkeys by oral administration and had an excellent toxicity profile (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Ingenol mebutate (IngMeb) is a topical agent approved for fielddirected treatment of AK with only 2-3 daily treatments. [6][7][8] Pretreating the skin with ablative fractional CO 2 laser (AFXL) has shown promise as an anti-cancer treatment, whereby uptake of topical photosensitizers is increased, and clinical outcome from photodynamic therapy is enhanced. 9,10 AFXL pretreatment may have the same potential to enhance treatment outcome with Ing-Meb, and it is therefore essential to evaluate safety and efficacy of treating AK with IngMeb delivered through AFXL channels.…”
Section: Editormentioning
confidence: 99%
“…Presently available topical AK treatments are time‐consuming, and cryotherapy may cause disturbing hypopigmentation disorders . Ingenol mebutate (IngMeb) is a topical agent approved for field‐directed treatment of AK with only 2–3 daily treatments . Pretreating the skin with ablative fractional CO 2 laser (AFXL) has shown promise as an anti‐cancer treatment, whereby uptake of topical photosensitizers is increased, and clinical outcome from photodynamic therapy is enhanced .…”
mentioning
confidence: 99%
“…On a slightly different note, NCT01926496 has recently been initiated to prospectively evaluate the risk of subjects with actinic keratosis treated with Aldara ® or ingenol mebutate (an FDA-approved substance commercialized as 0.015% or 0.05% cream under the trade name Picato ® ), 152 - 154 to develop squamous cell carcinoma (NCT01926496). In addition, BCG is currently being evaluated as a standalone therapeutic intervention or combined with a viral vector encoding mucin 1 (MUC1), carcinoembryonic antigen (CEA) and three immunostimulatory molecules, i.e., CD80 (also known as B7–1), CD58 (also known as LFA-3) and intercellular adhesion molecule 1 (ICAM1), 155 - 159 in adults with high-grade non-invasive bladder carcinoma who failed at least 1 course of BCG (NCT02015104).…”
Section: Update On Ongoing Clinical Trialsmentioning
confidence: 99%